ETIKA PELAKSANAAN TUGAS DAN JABATAN KEJAKSAAN - Fauzan Al-Asari; M. Royyan Fatullah; M. Hafidz Nur Fajri; Liza Novia Anggraini (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Indonesia, as a nation governed by law, as affirmed in the 1945 Constitution of the Republic of Indonesia, mandates respect for legal principles. The prosecution service, as an integral part of the legal system, plays a crucial role in law enforcement and justice. This study explores the ethics in the performance of prosecutorial duties and roles, encompassing personal ethics, task execution ethics, service ethics, and workplace relationship ethics. The aim of this research is to understand various aspects of prosecutorial ethics, including how prosecutors should behave in carrying out their duties and maintaining the integrity of their profession. Additionally, the study discusses the role and responsibility of prosecutorial oversight institutions in enforcing the code of ethics, ensuring that the prosecution service functions independently and fairly. The results indicate that professional ethics serve as the moral foundation for prosecutors in their duties, reflecting integrity, honesty, justice, and responsibility. This ethics framework is expected to maintain public trust in the judicial system and ensure that justice is properly administered. The study also highlights the importance of the code of ethics in preventing conflicts of interest and promoting harmonious cooperation among prosecutorial colleagues. The benefits of this research include providing insights for students and readers about the importance of ethics in the prosecutorial profession and how these ethics contribute to fair and dignified law enforcement in Indonesia. Additionally, this study aims to aid in the development of better policies to support professional and ethical law enforcement.